ER stress-induced YAP upregulation leads to chondrocyte phenotype loss in age-related osteoarthritis - Gao, Yanchun; Wei, Haifeng; Peng, Xiaoyuan; Wang, Chenchen; Zhu, Hongyi; Yin, Junhui (Frontiers in Pharmacology, 2024)
Background: Osteoarthritis (OA) is a common degenerative joint disease, leading to pain and restricted mobility. Age-related endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of OA, but the underlying mechanisms remain unclear.This study aims to explore the relationship between age-related ER stress, YAP overexpression, and chondrocyte phenotype loss in the development of OA. Methods:Cartilage samples were collected from patients undergoing amputation, and age-related ER stress markers and YAP expression were assessed using immunohistochemical staining and qPCR. Transgenic mice with cartilage-specific YAP overexpression (YAP OE ) were created, and Pamrevlumab was administered to evaluate its therapeutic effects. Results: Higher expression of ER stress markers and YAP were showed in aged tissues compared to younger tissues. YAP overexpression led to decreased levels of cartilage phenotype markers and increased osteogenesis-related proteins. In vivo, YAP OE mice exhibited OA-like cartilage degeneration, which was mitigated by Pamrevlumab treatment. Conclusions: Age-related ER stress induces YAP overexpression, contributing to OA pathogenesis. Pamrevlumab effectively prevents this phenotype loss in YAP OE mice, suggesting its potential as a therapeutic agent for OA. These findings provide new insights into the molecular mechanisms of OA and highlight the importance of targeting the ER stress-YAP-CTGF signaling pathway in OA treatment and prevention.